Penerapan Model Problem Based Learning Untuk Meningkatan Hasil Belajar pada Pembelajaran Tematik Terpadu di Kelas V Sekolah Dasar - Ersya, Muhammad Afif; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study attempts to improve student learning outcomes s in integrated thematic learning through used the of Problem Based Learning (PBL) model to the fourth grade students of SDN 23 Ujung Gurun Kota Padang. This is a PTK typified study with the implementation of two approaches, namely qualitative and quantitative. conducted in two cycles, with three meetings, covering four stages, namely planning, implementation, observation, and reflection. This study was conducted at SDN 23 Ujung Gurun Kota Padang to 21 students. The results of the study: (1) percentage The learning plan, namely 84,72% (Good) to 94,44% (Very Good). (2) The implementation of learning from  aspect of teacher, of 75% (enough) to 92.85% (Very Good). (3) The aspects of students of 75% (enough) to 92.85% (Very Good). (4) the student learning outcomes of 68,25% (enough) to 86% (Good). It can be concluded that the Problem Based Learning model can possibly improve student learning outcomes.